Cap-like structures in bacterial RNA and epitranscriptomic modification - Jäschke, Andres; Höfer, Katharina; Nübel, Gabriele; Frindert, Jens (Current opinion in microbiology, 2016)
The absence of capped RNA is considered as a hallmark of prokaryotic gene expression. Recent developments combine next-generation sequencing with a chemo-enzymatic capture step that allows the enrichment of rare 5′-modified RNA from bacteria. This approach identified covalent cap-like linkage of a specific set of small RNAs to the ubiquitous redox cofactor NAD, and a profound influence of this modification on RNA turnover. The modification revealed an unexpected connection between redox biology and RNA processing. We discuss possible roles of the NAD modification as well as broader implications for structurally related cofactors and metabolites which may also be linked to RNAs, leading to a new epitranscriptomic layer of information encoded in the chemical structure of the attached cofactors.
Gesehen am 30.04.2020